Natural Rabies Infection in a Domestic Fowl (Gallus domesticus): A Report from India. - Julie Baby; Reeta Subramaniam Mani; Swapna Susan Abraham; Asha T Thankappan; Prasad Madhavan Pillai; Ashwini Manoor Anand; Shampur Narayan Madhusudana; Jayachandran Ramachandran; Sachin Sreekumar (Public Library of Science (PLoS), 2015)
Rabies is a fatal encephalitis caused by viruses belonging to the genus Lyssavirus of the family Rhabdoviridae. It is a viral disease primarily affecting mammals, though all warm blooded animals are susceptible. Experimental rabies virus infection in birds has been reported, but naturally occurring infection of birds has been documented very rarely.The carcass of a domestic fowl (Gallus domesticus), which had been bitten by a stray dog one month back, was brought to the rabies diagnostic laboratory. A necropsy was performed and the brain tissue obtained was subjected to laboratory tests for rabies. The brain tissue was positive for rabies viral antigens by fluorescent antibody test (FAT) confirming a diagnosis of rabies. Phylogenetic analysis based on nucleoprotein gene sequencing revealed that the rabies virus strain from the domestic fowl belonged to a distinct and relatively rare Indian subcontinent lineage.This case of naturally acquired rabies infection in a bird species, Gallus domesticus, being reported for the first time in India, was identified from an area which has a significant stray dog population and is highly endemic for canine rabies. It indicates that spill over of infection even to an unusual host is possible in highly endemic areas. Lack of any clinical signs, and fewer opportunities for diagnostic laboratory testing of suspected rabies in birds, may be the reason for disease in these species being undiagnosed and probably under-reported. Butchering and handling of rabies virus- infected poultry may pose a potential exposure risk.